Journal of Artificial Organs The Official Journal of the Japanese Society for Artificial Organs - Sawa, Yoshiki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
The aim of the Journal of Artificial Organs is to introduce to colleagues worldwide a broad spectrum of important new achievements in the field of artificial organs, ranging from fundamental research to clinical applications. The scope of the Journal of Artificial Organs encompasses but is not restricted to blood purification, cardiovascular intervention, biomaterials, and artificial metabolic organs. Additionally, the journal will cover technical and industrial innovations. Membership in the Japanese Society for Artificial Organs is not a prerequisite for submission. .
Keywords: Nephrology; Cardiac surgery; Biomedical engineering; Cardiac Surgery; Nephrology; Biomedical Engineering and Bioengineering